Liquid stock as an acquisition currency - Huang, Sheng; Maharjan, Johan; Nanda, Vikram (Journal of Corporate Finance, 2024)
We examine how stock liquidity affects acquisitions. We hypothesize that liquidity enhances acquirer stock as an acquisition currency, especially when the target is relatively less liquid. As hypothesized, we find that more liquid firms have a greater likelihood of making stock acquisitions. Further, the difference in stock liquidity between acquirer and target firms increases payment with stock, reduces acquisition premiums, and improves acquirer announcement returns in equity deals. Consequently, firms take steps to improve stock liquidity prior to stock acquisitions. We use policy initiatives as exogenous shocks to firm liquidity to show that liquidity effects on acquisitions are plausibly causal.